Динаміка складу та взаємовідносини видів рослин в кормових агрофітоценозах - Шевчук, О.М.; Юрченко, І.Т. (Промышленная ботаника, 2002)
The data of many years investigations of sown fodder agrophytocenoses are presented in the article. The dynamics of such agrophytocenoses specific composition has been under study. Two main species fractions have been defined: cultigens and weeds and two subfractions - obligatory and facultative weeds, the character of changes in their number with the cenoses age being revealed. The data obtained testify to a renewal succession of man-made agrophytocenoses into natural. Interrelations between species in agrophytocenoses of different age have been studied by method of correlation. According to this index, the eight year old agrophytocenosis is nearing to natural one and presents a system of species with a complicated character of interrelations.